Epidemiology, Clinical Features and Prognostic Factors of Pediatric SARS-CoV-2 Infection: Results From an Italian Multicenter Study - Garazzino, Silvia; Lo Vecchio, Andrea; Pierantoni, Luca; Calò Carducci, Francesca Ippolita; Marchetti, Federico; Meini, Antonella; Castagnola, Elio; Vergine, Gianluca; Donà, Daniele; Bosis, Samantha; Dodi, Icilio; Venturini, Elisabetta; et al. (Frontiers in Pediatrics, 2021)
Abstract Background. Many aspects of SARS-CoV-2 infection in children and adolescents remain unclear and optimal treatment is debated. The objective of our study was to investigate epidemiological, clinical and therapeutic characteristics of pediatric SARS-CoV-2 infection, focusing on risk factors for complicated and critical disease. Methods. The present multicenter Italian study was promoted by the Italian Society of Pediatric Infectious Diseases, involving both pediatric hospitals and general pediatricians/family doctors. All subjects under 18 years of age with documented SARS-CoV-2 infection and referred to the coordinating center were enrolled from March 2020. Results. As of 15 September 2020, 759 children were enrolled (median age 7.2 years, IQR 1.4;12.4). Among the 688 symptomatic children, fever was the most common symptom (81.9%). Barely 47% of children were hospitalized for COVID-19. Age was inversely related to hospital admission (p < 0.01) and linearly to length of stay (p = 0.014). 149 children (19.6%) developed complications. Comorbidities were risk factors for complications (p < 0.001). Viral coinfections, underlying clinical conditions, age 5 - 9 years and lymphopenia were statistically related to ICU admission (p< 0.05). Conclusions. Complications of COVID-19 in children are related to comorbidities and increase with age. Viral co-infections are additional risk factors for disease progression and multisystem inflammatory syndrome temporarily related to COVID-19 (MIS-C) for ICU admission.